Mathematical modeling for determining the potency of bovine tuberculin purified protein derivative (P.P.D.) - Viviana Ciuca; Victorita Burghelea; Mihai Danes; Viorel V. Safta; Olga Casu; Ramona Niculicioiu (Medicamentul Veterinar)
Bovine tuberculin purified protein derivative (bovine tuberculin PPD) is a preparation obtained from the heat-treated products of growth and lysis of Mycobacterium bovis, strain AN5, purified and solubilized into a liquid preservative, buffered, glycerinate and phenolate, so that the diagnostic product contain at least 20,000 international units. The main characteristic of commercial product is “revelatory power” or potency. The animals infected with Mycobacterium bovis develop delayed hypersensitivity which can be revealed in vivo by skin allergic test. The validation study aims to demonstrate the determination of the potency of the bovine tuberculin PPD, by comparing the reactions produced in guinea pigs sensitized by the intradermal injection of a series of dilutions of the product to be examined with those produced by a reference standard calibrated in international units, it is an appropriate analytical method, reproducible and meets the quality requirements of diagnostic reagents. The paper establishes the performance characteristics of the method considered and identify the factors that influence these characteristics. The diameters of the lesions, directly proportional to the logarithm of the concentration of the tuberculin, measured and calculated using statistical methods (Combistats Soft). The test is not valid unless the confidence limits (P=0.95) are not less than 50 per cent and not more than 200 per cent of the estimated potency. The estimated potency is not less than 66 per cent and not more than 150 per cent of the stated potency. The stated potency is not less than 20,000 international units. The validation procedure includes details on protocol working to determine the potency of the tuberculin A, validation criteria, experimental results, mathematical modeling for determining the potency, inter-laboratory comparisons.